SYNTACTIC STRUCTURES OF COMPLEX SENTENCES: SIMILARITIES AND DIFFERENCES BETWEEN UZBEK AND ENGLISH - Mansurova Surayyo Haydar qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Complex sentences represent a sophisticated layer of linguistic organization that is vital for expressing multifaceted thoughts, relationships of dependence, and nuanced connections between ideas. The syntactic structures of such sentences allow speakers and writers to encode logical, temporal, causal, and conditional relationships with remarkable precision, going far beyond the capabilities of simple or compound sentences. Comparing the syntactic structures of complex sentences in Uzbek and English is a profound endeavor that unveils deep-rooted principles of each language, explains much about their typological profiles, and reflects diverse communicative traditions.